Roy's Turkish Delight: Football, Nationalism and the Representation of Turkey in the British Sports Media - Turksoy, Nilufer (Routledge Journals, Taylor & Francis Ltd, 2020)
A large body of literature in representational studies reflects a deep professional concern over the negative effect of the role of the media in representing significant Others. Western media's coverage of an international event, in this case, a football competition, raises some ethical questions about the choice of specific lexical items and textual contents. Drawing on the work of Stuart Hall's representation theory, this article examines how Turkey, a nation located on the semi-periphery of Europe, is represented in Western media outlets. By looking at the role that sections of the British sports press plays in their construction of the Turkish national identity, I evaluate the Euro 2016 and Euro 2004 reporting of the UEFA European Championship qualifying matches between Turkey and England. I apply a combination of lexical and narrative analysis, and I question the way that Turkey is represented in the British sport texts. The style and language used in the presentation of football games reveals that British media outlets are prone to present England's politically and economically powerful position, and its cultural superiority over Turkey. Findings also suggest that the discourse of the West and the Rest is alive in the modern world.
Keywords: Representation of the Other; journalism; national identity; stereotyping; England and Turkey; British sports media; football